Dutch health websites and their ability to inform people with low health literacy. Issue 11 (November 2017) - Meppelink, Corine S.; van Weert, Julia C.M.; Brosius, Anna; Smit, Edith G.
Highlights: Dutch OHI is not optimally designed for people with low health literacy. Only a third of the pages have informative images, videos and narration are scarce. Texts on most webpages are too difficult for people with low health literacy. e-Health possibilities, such as tailored information, are infrequently used. There is a lack of quality labels and other reliability indicators in Dutch OHI. Abstract: Objective: To evaluate whether Dutch online health information (OHI) generally reflects message elements that support information processing and understanding among people with low health literacy. Methods: We content-analyzed one hundred Dutch webpages about Ebola, fibromyalgia, ALS, losing weight, borderline personality disorder, hemorrhoids, ADD, bladder infection, shingles, and chicken pox. The codebook covered the following domains: images and videos, readability level, Suitability Assessment of Materials (SAM), advertising, interactive features, and reliability cues. Results: Thirty-seven webpages contained informative images that visualized the text. Twelve webpages incorporated videos, six of which were animations. Readability varied widely, but 79.2% of the texts exceeded the recommended B1 level. Half of the webpages had inadequate SAM scores; five were classified as superior. Interactive features were infrequently used. Many webpages included only a few elements that help users evaluate the reliability of OHI. Four presented a quality label. Conclusion: Over a wide range of health-related topics, Dutch OHI does not generally contain message elements that improve information processing among people with low health literacy. Practice implications: Communication professionals should make better use of digital message features. Videos, narration, and interactivity are scarcely used but can be valuable for people with low health literacy.